Does anyone have a projection matrix knocking around that will do

y’ = (y/2) - (x/2) + Z

x’ = x + y

z’ = z

My maths is just too poor to figure it out in a reasonable timeframe.

Cas

Does anyone have a projection matrix knocking around that will do

y’ = (y/2) - (x/2) + Z

x’ = x + y

z’ = z

My maths is just too poor to figure it out in a reasonable timeframe.

Cas

v’ = M * v for your case looks like this:

x’ 1 1 0 x

( y’ )= ( -0.5 0.5 1 ) * ( y )

z’ 0 0 1 z

resp. for 4x4 GL_PROJECTION matrix.

x’ 1 1 0 0 x

( y’ )= ( -0.5 0.5 1 0) * ( y )

z’ 0 0 1 0 z

w’ 0 0 0 1 w

[This message has been edited by Relic (edited 07-06-2000).]

Relic, you’re a star.

I’ll have a play with it.